Verhalten ausgewählter metaboler und hormoneller Parameter während eines Dreifachlangtriathlons - Volk, O.; Neumann, G. (Österreichisches Journal für Sportmedizin, 2000)
Nine athletes were examined during a triple long triathlon of 48 hours duration on average. The exercise lead to a hypervolemina. Hypoglycemic regulations were not found. The fat metabolism was dominant. Sign of insufficient availability of carbohydrates was the significant increase of beta-hydroxybutyrate. The protein catabolism was characterized by a significant increase in serum urea and the ratio of cortisol/testosterone. The summed amino acids decreased significantly. Extreme endurance exercise can be completed by a stable metabolism with continuously energy intake.